Printed pressure housings for underwater applications. (1st February 2016) - Breddermann, K.; Drescher, P.; Polzin, C.; Seitz, H.; Paschen, M.
Abstract: In order to investigate the capability of additive manufacturing technologies to build pressure housings, hemispheres made of titanium and ceramic with a nominal outer diameter of 70 mm were built on 3D printer systems, evaluated, and tested in a pressure tank. Titanium hemispheres expected to withstand an external pressure of 10 MPa started buckling at 6 MPa. A stiffened titanium hemisphere which was expected to withstand 24 MPa collapsed at 30 MPa. A ceramic hemisphere could not be tested to collapse since the measurement technique was not rated to withstand an external pressure above 30 MPa. Abstract : Highlights: Pressure housings for underwater applications were built in an additive manufacturing process from titanium and ceramic. The dimensional accuracy and surface finish was evaluated. The housings were tested in a pressure vessel. The housings show promising performance and have a satisfying weight to displacement ratio.